The Value of Theology in a Scientific Age - Keogh, Gary (New blackfriars, 2015)
The value of theology as a discipline has been challenged in recent years by a number of high-profile scientists, most prominently perhaps Stephen Hawking and Richard Dawkins. It has been questioned whether theology can bring anything to the table, particularly when compared with the clearly evident successes of modern science. This paper will take this challenge seriously and explore what value theology may have in the context of a scientific age, where the successes of the sciences have clearly reshaped how we think about the world. It will argue that theology offers a space and a language for discourse on the ineffable and intangible aspects of human experience, and can address the implicit philosophical and theological connotations of the scientific worldview.